Principle of the Right of Peoples to Self-determination Between Theory and Practice (Case Study of Palestine) - Djameleddine, Denden (Journal of Legal Studies and Researches, 2022)
The international consecration of the principle of the right of peoples to self-determination was at the level of charters of global and regional international conventions on human rights. Consequently, the use of this right as an international mechanism is intended to achieve the independence of the countries under colonial control. This research paper aims to shed light on the concept of the right to self-determination in international law and examines the issue of the struggle of the Palestinian people to determine their own destiny in light of international practice.